2011
DOI: 10.1111/j.1525-1470.2011.01234.x
|View full text |Cite
|
Sign up to set email alerts
|

Recalcitrant Palmoplantar Pustular Psoriasis Treated with Etanercept

Abstract: We report a 10-year-old boy presenting with palmoplantar pustular psoriasis, resistant to topical and systemic treatments, who was successfully treated with subcutaneous etanercept (0.4 mg/kg) twice a week for 1 month. Maintenance therapy was extended for 18 months in combination with near ultraviolet light therapy without any adverse effect. Etanercept may be a safe and effective alternative for severe palmoplantar pustular psoriasis in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 5 publications
0
22
0
2
Order By: Relevance
“…3,4 PPP can present alone, or in association with psoriasis vulgaris [palmoplantar pustular psoriasis (PPPP)]. 4,[7][8][9][10][11][12] We present our experience with ustekinumab in five patients with severe refractory PPPP. 5,6 Biological agents are highly effective in moderate-to-severe psoriasis vulgaris, and their efficacy in nonpustular palmoplantar psoriasis has been shown in a clinical trial, 7 but only sporadic cases and very few reports have been published in support of their possible therapeutic efficacy in PPP and PPPP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 PPP can present alone, or in association with psoriasis vulgaris [palmoplantar pustular psoriasis (PPPP)]. 4,[7][8][9][10][11][12] We present our experience with ustekinumab in five patients with severe refractory PPPP. 5,6 Biological agents are highly effective in moderate-to-severe psoriasis vulgaris, and their efficacy in nonpustular palmoplantar psoriasis has been shown in a clinical trial, 7 but only sporadic cases and very few reports have been published in support of their possible therapeutic efficacy in PPP and PPPP.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Biological agents are highly effective in moderate-to-severe psoriasis vulgaris, and their efficacy in nonpustular palmoplantar psoriasis has been shown in a clinical trial, 7 but only sporadic cases and very few reports have been published in support of their possible therapeutic efficacy in PPP and PPPP. 4,[7][8][9][10][11][12] We present our experience with ustekinumab in five patients with severe refractory PPPP.…”
Section: Discussionmentioning
confidence: 99%
“…In two large studies of JIA, one with a duration up to 8 years, the safety profile of etanercept was almost the same as in pediatric psoriasis, although conclusions based on different disease populations could be biased 61,62. According to several case reports and expert opinion, etanercept has also a favorable therapeutic profile in the treatment of severe erythrodermic and pustular pediatric psoriasis 20,5860,63. It is interesting to note that 70% of participants in a European expert group consensus consider etanercept as first-line treatment of juvenile chronic plaque psoriasis due to its strong efficacy, excellent tolerability, and good safety profile 20…”
Section: Management Of Psoriasis In Adolescencementioning
confidence: 99%
“…4 Fourteen new studies were found. 60,[68][69][70][71][72][73][74][75][76][77][78][79][80] Seven studies were exluded, 60,68,[70][71][72]74,76 because of an unclear outcome measure and/or systemic combination therapy (n = 4), 60,68,70,74 subgroup analyses of an original double-blind randomized controlled trial (RCT) 61 which was already mentioned in our previous review 4 (n = 2), 72,76 and only quality of life (Qol) outcomes of the same previously mentioned cohort (n = 1). 71 In the present review, new publications on the cohort described in the 48-week phase III double-blind RCT (LOE1b) 61 were included, containing long-term data.…”
Section: Etanerceptmentioning
confidence: 99%